Role of amino acid metabolism in mitochondrial homeostasis - Li, Qiaochu; Hoppe, Thorsten (Frontiers in Cell and Developmental Biology, 2023)
Mitochondria are central hubs for energy production, metabolism and cellular signal transduction in eukaryotic cells. Maintenance of mitochondrial homeostasis is important for cellular function and survival. In particular, cellular metabolic state is in constant communication with mitochondrial homeostasis. One of the most important metabolic processes that provide energy in the cell is amino acid metabolism. Almost all of the 20 amino acids that serve as the building blocks of proteins are produced or degraded in the mitochondria. The synthesis of the amino acids aspartate and arginine depends on the activity of the respiratory chain, which is essential for cell proliferation. The degradation of branched-chain amino acids (BCAAs) mainly occurs in the mitochondrial matrix, contributing to energy metabolism, mitochondrial biogenesis, as well as protein quality control in both mitochondria and cytosol. Dietary supplementation or restriction of amino acids in worms, flies and mice modulates lifespan and health, which has been associated with changes in mitochondrial biogenesis, antioxidant response, as well as the activity of tricarboxylic acid (TCA) cycle and respiratory chain. Consequently, impaired amino acid metabolism has been associated with both primary mitochondrial diseases and diseases with mitochondrial dysfunction such as cancer. Here, we present recent observations on the crosstalk between amino acid metabolism and mitochondrial homeostasis, summarise the underlying molecular mechanisms to date, and discuss their role in cellular functions and organismal physiology.